Draft BS A 109. Bolts, shear, hexagonal heads, close tolerance shank, unified threads, alloy steel, cadmium plated (on head and thread only). Specification. Classification Rm = 127, 600 – 156, 600 lbf/in2 (880 – 1080 MPa) at Ambient temperature | +190°C (31st August 2023) - British Standards Institution,
No abstract available